Comparison of Fluorescence, 31P NMR, and 7Li NMR Spectroscopic Methods for Investigating Li+/Mg2+ Competition for Biomolecules - Amari, Louis (1999)
The biochemical action of lithium in the treatment of manic-depressive illness is still unknown. One hypothesis is that Li+ competes for Mg2+-binding sites in biomolecules. We report here our studies on metal ion competition by three distinct methods: fluorescence, 31P NMR, and 7Li NMR spectroscopy, using ATP as a model ligand. By fluorescence spectroscopy, we used the dye, furaptra, by measuring the increases in Mg2+ levels in an ATP solution as Li+ levels were increased in the solution. This increase in Mg2+ levels was indicated by increases in the fluorescence intensity ratio (335/370) of furaptra. By 31P NMR spectroscopy, this competition was demonstrated by changes in the 31P NMR spectrum of ATP. The Li+/Mg2+ competition was indicated by predictable changes in the separation between the [alpha] and [beta] resonances of the phosphates of ATP. For 7Li NMR spectroscopy, spin-lattice relaxation measurements were used, which provided free Li+ concentrations that could be used for determining the free Mg2+ values in ATP solutions. The values of the free Mg2+ concentrations obtained by all three methods were in good agreement. The fluorescence and 7Li NMR methods, however, proved to be more sensitive to low concentrations of Li+ than the 31P NMR method.